CD8+ T Lymphocytes: Crucial Players in Sjögren’s Syndrome - Zhou, Huimin; Yang, Jun; Tian, Jie; Wang, Shengjun (Frontiers in Immunology, 2021)
Primary Sjögren’s syndrome (pSS) is a chronic autoimmune disease associated with damage to multiple organs and glands. The most common clinical manifestations are dry eyes, dry mouth and enlarged salivary glands. Currently, CD4+ T lymphocytes are considered to be key factors in the immunopathogenesis of pSS, but various studies have shown that CD8+ T lymphocytes contribute to acicular injury in exocrine glands. Therefore, in this review, we discussed the classification and features of CD8+ T lymphocytes, specifically describing the role of CD8+ T lymphocytes in disease pathophysiology. Furthermore, we presented treatment strategies targeting CD8+ T cells to capitalize on the pathogenic and regulatory potential of CD8+ T lymphocytes in pSS to provide promising new strategies for this inflammatory disease.